2019
DOI: 10.3390/ijerph16152718
|View full text |Cite
|
Sign up to set email alerts
|

School Food Policies Related to Soft Drink and Fruit Juice Consumption as a Function of Education Type in Flanders, Belgium

Abstract: Recent data on erosive tooth wear (ETW) in Belgium have associated a vocational/technical type of education with ETW risk. Since the role of schools is essential to the promotion of healthy diets, this study aimed to investigate school food policies (SFP) related to soft drink and fruit juice consumption and to detect differences among schools in Flanders, Belgium (BE-F). An online questionnaire related to the control of acidic beverages and promotion of healthy drinking habits was sent to all Flemish secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Consumption of red dragon fruit that is not excessive does not cause discoloration and a decrease in SAFC value. Red dragon fruit is a fruit that has a lot of good content for the body, such as being rich in vitamin C and can increase metabolism in the body [16] but education is needed for patients to drink water and brush their teeth after consuming red dragon fruit [37]. It is also suggested that patients could use straw while consuming red dragon fruit juice.…”
Section: Resultsmentioning
confidence: 99%
“…Consumption of red dragon fruit that is not excessive does not cause discoloration and a decrease in SAFC value. Red dragon fruit is a fruit that has a lot of good content for the body, such as being rich in vitamin C and can increase metabolism in the body [16] but education is needed for patients to drink water and brush their teeth after consuming red dragon fruit [37]. It is also suggested that patients could use straw while consuming red dragon fruit juice.…”
Section: Resultsmentioning
confidence: 99%